ANALISIS PERBEDAAN HARGA SAHAM, VOLUME PERDAGANGAN SAHAM DAN KAPITALISASI PASAR PADA SEKTOR MANUFAKTUR SEBELUM DAN SELAMA PANDEMI COVID-19 - Gracelyn Aglia; Rousilita Suhendah (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
The purpose of this study is to analyze on whether there are significant differences in stock prices, stock trading volume and market capitalization on manufacturing companies listed in Indonesia Stock Exchange 2020 before and during COVID-19 pandemic. The research method used is quantitative method. The sampling method used is purposive sampling where there are 183 manufacturing companies that are the research sample with an 84-day research period which are analyzed using Microsoft Excel and SPSS 25.0. The data methods used in this study are Kolmogorov Smirnov (K-S) normality test, descriptive statistics analysis and Wilcoxon Signed-Rank Test. The results of this study showed that there are significant differences in stock price, stock trading volume and market capitalization in the manufacturing sector before and during the COVID-19 pandemic.